PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS V DI MI AL-FALAH - Nurlelah, Nurlelah; Rahman, Imas Kania; Sobari , Ahmad (ATTA`DIB, 2019)
Education will evolve continuously following the times. As human beings who have creative and innovative potential will surely follow the development of an increasingly advanced era in order not to be left behind. Every teacher is expected to have skills in teaching one of them is to choose a learning model so that learning can be conveyed interestingly. The purpose of this research is to know the students ' learning Achievement in social studies subjects (IPS} in 5th grade at MI Al-Falah, knowing the application of the Type Cooperative learning model in the IPS subject and knowing the influence of the learning model implementation The type of jigsaw to students ' learning achievements. In this study using the quasi experiment method, according to Arikunto research experiments is a way to find causal relationships (relationship clause) between two factors intentionally posed by researchers by eliminating or Reduce or set aside other factors that interfere. The type of research is Non Equivalent Design, using pretest and post test. The value of the experiment class pretest is 2264 and has an average of 59.08. Then after treatment the total value of the students increased to 3032 with an average value of 84.22. So the average value increase of 25.14 points. The pretests value of the control class is 2264 with an average value of 62.89. Then, given the treatment using the conventional amount of value to 2809 with an average value of 78.02. So there is an increase in the average value of 15.13 points.